2020
DOI: 10.4103/jmp.jmp_25_20
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of skin doses for retrofit prototype multileaf collimators designed for telecobalt therapy machine

Abstract: Aim: The objective of this study was to evaluate skin dose based on retrofit prototype multileaf collimators (MLCs), designed for cobalt-60 teletherapy machine. Since patient's skin is sensitive to radiation, evaluation of skin dose is of utmost importance for investigating the risk of late effects. Materials and Methods: Measurements were performed with a Phoenix cobalt-60 teletherapy machine and the detector used was EBT3 radiochromic film. The experiments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Accurate determination of the surface dose is a difficult but important task for ensuring the proper treatment of patients. The percentage skin dose values estimated in this study (and shown in Fig 7) are within the range of values predicted in previous studies [70][71][72][73]. In an in vivo dosimetric assessments for an open field 10 cm x 10 cm and SSD of 100 cm, surface doses of 30%, 29.1%, 27.8%, 29.3%, and 29.9% were determined for five telecobalt machines: Equinox-80, Elite-80, Th-780C, Th-780, and Bhabhatron-II respectively [70].…”
Section: Skin Dose Assessmentsupporting
confidence: 90%
See 1 more Smart Citation
“…Accurate determination of the surface dose is a difficult but important task for ensuring the proper treatment of patients. The percentage skin dose values estimated in this study (and shown in Fig 7) are within the range of values predicted in previous studies [70][71][72][73]. In an in vivo dosimetric assessments for an open field 10 cm x 10 cm and SSD of 100 cm, surface doses of 30%, 29.1%, 27.8%, 29.3%, and 29.9% were determined for five telecobalt machines: Equinox-80, Elite-80, Th-780C, Th-780, and Bhabhatron-II respectively [70].…”
Section: Skin Dose Assessmentsupporting
confidence: 90%
“…From the range of skin dose values predicted in previous studies (from~20% to 30%), the percentage skin dose estimated in this study (24%) under the same irradiation conditions can be considered reasonable. Furthermore, Rani, Ayyangar [73] evaluated the skin dose for a cobalt-60 teletherapy machine and observed that for an open field of 10 cm × 10 cm at 80 cm SSD, the % skin dose was 31.98%. The percentage of skin dose reported in their study was slightly higher than that determined in this research (29.33%) under the same irradiation conditions (open field, field size and SSD).…”
Section: Skin Dose Assessmentmentioning
confidence: 99%